Establishing a dedicated toxicology unit reduces length of stay of poisoned patients and saves hospital bed days. (7th March 2017) - Isoardi, Katherine Z; Armitage, Melanie C; Harris, Keith; Page, Colin B
Abstract: Objective: This study evaluates the effect on the average length of stay (LOS), relative stay index (RSI), bed days and costs saved following the establishment of a dedicated clinical toxicology unit in an Australian tertiary referral hospital. Methods: This retrospective descriptive study uses Health Roundtable and other state and federal data to compare the average LOS, RSI, estimated bed days and costs saved by patients admitted with a diagnosis‐related group (DRG) of X62 (Poisoning/Toxic Effects of Drugs and Other Substances), over the 4 year period 2012–2015. This period corresponds to before and after the introduction of the clinical toxicology unit in February 2014 at the Princess Alexandra Hospital, a tertiary referral teaching hospital in Brisbane, Queensland, Australia. Results: There was a reduction in the average LOS and RSI from 2.1 days and 122% in 2012 to 0.9 days and 52% in 2015, respectively. This reduction correlates with a reduction in 1350 bed days and a saving of $2.25 million over the 2 year period 2014–2015 since the clinical toxicology unit was established. Conclusion: The reduction in average LOS is similar to results previously published by two Australian toxicology units over 15 years ago. Despite changes in healthcare delivery since this time, these results continue to support the efficiency and associated cost saving of a dedicated toxicology unit in managing poisoned patients.